2019
DOI: 10.1093/icb/icz151
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Claw Shape in a Transcontinental Lizard Radiation

Abstract: Species occupying similar selective environments often share similar phenotypes as the result of natural selection. Recent discoveries, however, have led to the understanding that phenotypes may also converge for other reasons than recurring selection. We argue that the vertebrate claw system constitute a promising but understudied model system for testing the adaptive nature of phenotypic, functional, and genetic convergence. In this study, we combine basic morphometrics and advanced techniques in form analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…Conversely, claw morphology in a variety of birds was considered to be independent of phylogeny and size by Glen and Bennett (2007) and it was recently found to be independent of both specifically in birds of prey, being linked more to biomechanics and relative prey size (Tsang et al, 2019). Another study found only a weak phylogenetic signal in lacertid claw morphology which did not interfere with attempts to link morphology with habitat use (Baeckens et al, 2019). Regardless of these findings and despite the incorporation of claw specimens from a wide variety of bird, mammal, and reptile species, covering a diverse range of phylogenetic, behavioral and size groups, the outcome of the LDA may be phylogenetically biased.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, claw morphology in a variety of birds was considered to be independent of phylogeny and size by Glen and Bennett (2007) and it was recently found to be independent of both specifically in birds of prey, being linked more to biomechanics and relative prey size (Tsang et al, 2019). Another study found only a weak phylogenetic signal in lacertid claw morphology which did not interfere with attempts to link morphology with habitat use (Baeckens et al, 2019). Regardless of these findings and despite the incorporation of claw specimens from a wide variety of bird, mammal, and reptile species, covering a diverse range of phylogenetic, behavioral and size groups, the outcome of the LDA may be phylogenetically biased.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, the use of geometric morphometric methods showed promise for separating aquatic/terrestrial, arboreal, and predatory birds (McIntosh, 2017) whereas another study found that these methods were unable to significantly separate birds into predatory, ground‐dwelling, and generalist groups (Hedrick et al, 2019). There have been few investigations into the functional morphology of reptile claws, most of which deal with narrow taxonomic groups (Baeckens et al, 2019; D'Amore et al, 2018; M. J. Tulli et al, 2009; Yuan et al, 2020; Yuan et al, 2019; Zani, 2000). This may be due to the relative dearth of information on reptile claw function in the natural history literature, especially compared to that which exists for birds and mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Ecological information concerning claws is not included in this review. This information can be found elsewhere (Baeckens et al, 2019; Zani, 2000). The review also presents some information on the patterns of immunolabeling detected in developing and adult claws, integrated from the molecular and proteomic data derived from the analyses of extracted claw proteins in some representative species of lizards, tuatara, turtles, and alligator.…”
Section: Introductionmentioning
confidence: 99%
“…The almost ubiquitous presence of variously shaped claws in amniotes indicates the fundamental importance of these horny structures for life on land. Claws were likely initial adaptations for moving efficiently on a muddy or more solid surface, and became useful for grasping, clinging, manipulating objects, fighting, and tearing (Zani, 2000; Homberger et al, 2009; Moyer, Zheng, & Schweitzer, 2016; Baeckens, Goeyers, & Van Damme, 2019; Figure 1e). The fossil record shows that claws were present in early amniotes of the Permian‐Carboniferous, both synapsids and sauropsids, and even in pre‐amniotes, such as Diadectes (Maddin & Reisz, 2007; Moyer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A daptations to habitats are responsible for some of the most striking examples of phenotypic evolution, driving profound shifts in morphology [1][2][3][4][5][6] , in shape diversity ('disparity') 7 and in rate of shape evolution 1,[8][9][10][11] . Adaptations to similar habitats also result in phenotypic convergence when responses to selection produce similar shifts in phenotypic optima across diverse clades 2,[12][13][14][15] , as in the body forms of pelagic fishes, ichthyosaurs and whales.…”
mentioning
confidence: 99%